2017
DOI: 10.5051/jpis.2017.47.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Effects of implant tilting and the loading direction on the displacement and micromotion of immediately loaded implants: an in vitro experiment and finite element analysis

Abstract: PurposeThe purpose of this study was to investigate the effects of implant tilting and the loading direction on the displacement and micromotion (relative displacement between the implant and bone) of immediately loaded implants by in vitro experiments and finite element analysis (FEA).MethodsSix artificial bone blocks were prepared. Six screw-type implants with a length of 10 mm and diameter of 4.3 mm were placed, with 3 positioned axially and 3 tilted. The tilted implants were 30° distally inclined to the ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…We previously demonstrated that the maximum micromotion of axial and tilted implants was very similar under vertical loading in the single implant model. 19 However, the effect of tilting the distal implants on micromotion in multipleimplant restorations has been unclear. The present findings indicate that tilted implant may have similar effects on micromotion compared with axial implant in a multiple-implant prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously demonstrated that the maximum micromotion of axial and tilted implants was very similar under vertical loading in the single implant model. 19 However, the effect of tilting the distal implants on micromotion in multipleimplant restorations has been unclear. The present findings indicate that tilted implant may have similar effects on micromotion compared with axial implant in a multiple-implant prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…37 In this study, contact interfaces with friction were simulated in the similar manner as previously published reports. 7,[11][12][13]17,19 Because material properties also have an important influence on the outcome, 38 Young's modulus for low-density cancellous bone was defined from preoperative patient data. 29 Implant configuration had a limited effect on micromotion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ISO 14801 (Dynamic loading test for endosseous dental implants) is currently the accepted standard for these tests, although it has severe limitations [6]. More and more authors suggest using Fine Element Analysis (FEA) as a substitute or in conjunction with the classical means of testing, as it can provide supplemental information and reduce testing time and costs [7,8]. Even the best results in laboratory testing and FEA cannot guarantee clinical success, if the basic biomechanical principles are not taken into consideration during insertion and loading.…”
Section: Background and Aimsmentioning
confidence: 99%